Awareness of Temporal Lag is Necessary for Motor–Visual Temporal Recalibration - Tsujita, Masaki; Ichikawa, Makoto (Frontiers in Integrative Neuroscience, 2016)
Consistent exposure to a temporal lag between observers’ voluntary action and its visual feedback induced recalibration of temporal order perception between a motor action and a visual stimulus. It remains unclear what kinds of processing underlie this motor–visual temporal recalibration. This study examined the necessity of motor–visual temporal recalibration for awareness of a temporal lag between a motor action and its visual feedback. In Experiment 1, we allocated observers to either the multiple-step or single-step lag conditions. In the multiple-step lag condition, we first inserted a small temporal lag and subsequently increased it with progress of the adaptation period, to make observers unaware of the temporal lag during the adaptation period. In the single-step lag condition, we instructed observers about the temporal lag before adaptation, and inserted a substantial temporal lag from the beginning of the adaptation period to ensure that they were aware of the temporal lag. We found significant recalibration only in the single-step lag condition. In Experiment 2, we exposed all observers to a substantial temporal lag from the beginning of adaptation period with no instruction about insertion of the temporal lag. We asked observers at the end of the experiment whether they were aware of the temporal lag. We found significant recalibration for only observers who were aware of the lag. These results suggest that awareness of the temporal lag plays a crucial role in motor–visual temporal recalibration.